2019
DOI: 10.1002/cne.24598
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh field imaging of myelin disease models: Toward specific markers of myelin integrity?

Abstract: Specific magnetic resonance imaging (MRI) markers of myelin are critical for the evaluation and development of regenerative therapies for demyelinating diseases. Several MRI methods have been developed for myelin imaging, based either on acquisition schemes or on mathematical modeling of the signal. They generally showed good sensitivity but validation for specificity toward myelin is still warranted to allow a reliable interpretation in an in vivo complex pathological environment. Experimental models of dys−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 82 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…These results included 50 review articles. From the 50 review articles, six were selected as relevant for both the topics of myelin and related MRI-histology comparisons ( Cohen-Adad, 2018 ; Laule and Moore, 2018 ; Laule et al, 2007 ; MacKay and Laule, 2016 ; Petiet et al, 2019 ; Turner, 2019 ). After the assessment, 58 original research studies were considered eligible, as shown in Appendix 1—table 1 (in the appendix) and Figure S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results included 50 review articles. From the 50 review articles, six were selected as relevant for both the topics of myelin and related MRI-histology comparisons ( Cohen-Adad, 2018 ; Laule and Moore, 2018 ; Laule et al, 2007 ; MacKay and Laule, 2016 ; Petiet et al, 2019 ; Turner, 2019 ). After the assessment, 58 original research studies were considered eligible, as shown in Appendix 1—table 1 (in the appendix) and Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being the most realistic approach, this comparison involves several methodological choices, from the specific technique used as a reference to the quantitative measure used to describe the relationship between MRI and histology. So far, a long list of studies have looked at MRI-histology comparisons ( Cohen-Adad, 2018 ; Laule and Moore, 2018 ; MacKay and Laule, 2016 ; Petiet et al, 2019 ), each of them focusing on a specific pathology and a few MRI measures.…”
Section: Introductionmentioning
confidence: 99%
“…These results included 50 review articles. From the 50 review articles, six were selected as relevant for both the topics of myelin and related MRI-histology comparisons (Cohen-Adad, 2018; Laule & Moore, 2018; Laule et al, 2007; A. L. MacKay & Laule, 2016; Petiet et al, 2019; Turner, 2019). After the assessment, 58 original research studies were considered eligible, as shown in Table A1 (in the appendix) and Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being the most realistic approach, this comparison involves several methodological choices, from the specific technique used as a reference to the quantitative measure used to describe the relationship between MRI and histology. So far, a long list of studies have looked at MRI-histology comparisons (Cohen-Adad, 2018; Laule & Moore, 2018; A. L. MacKay & Laule, 2016; Petiet et al, 2019), each of them focusing on a specific pathology and a few MRI measures.…”
Section: Introductionmentioning
confidence: 99%
“…The use of qMRI metrics to weight the connectome could have important implications for many applications. qMRI offers several techniques that are sensitive to myelin (Laule et al, 2007;Petiet et al, 2019), such as magnetization transfer, myelin water imaging, or relaxometry (for a complete list see (Heath et al, 2018)). Additionally, these techniques could be used to estimate the conduction velocity and conduction delays, and to incorporate these metrics as weights in the connectome.…”
Section: Discussionmentioning
confidence: 99%